Flaviporus albus (Steccherinaceae), a new species from southern China based on morphological and phylogenetic evidence - Wei, Qiu-Lu; Zheng, Hai-Fu; Shao, Yuan-Yuan; Rasheed, Usman; Huang, Hai-Si; Huang, Fu-Chang; Liu, Bin (Phytotaxa, 2023)
Flaviporus is a small genus within the wood-inhabiting family Steccherinaceae. Macroscopically, it is characterized by watery and resinous basidiomes that become hard and tend to shrink when dried, and microscopically by agglutinated hyphae that are difficult to observe. The present study proposes Flaviporus albus sp. nov. as a new species based on morphological and phylogenetic evidence. It is characterized by a white to cream pileus surface, small pores (10–14 per mm) with irregular dissepiments, and the presence of rather thin-walled to thick-walled skeletocystidia. The basidiospores are broadly ellipsoid to subglobose, measuring 2.1–2.6×1.7–2.3 μm, commonly with an oil drop, hyaline and have a thickened wall. These basidiospores do not show any reaction to Melzer’s or Cotton Blue. Furthermore, this study presents a key to the globally known species of Flaviporus.